Association of neighborhood greenness with self-perceived stress, depression and anxiety symptoms in older U.S adults. - Pun, Vivian C.; Manjourides, Justin.; Suh, Helen H. (2018)
Background: Neighborhood environment, such as green vegetation, has been shown to play a role in coping with stress and mental ill health. Yet, epidemiological evidence of the association between greenness and mental health is inconsistent.; Keywords: Green space, Perceived stress, Anxiety, Depression, Mediation, Effect modification.; Springer Open.